Dual-port laparoscopic myomectomy: a balanced yet potentially more optimal surgical approach - Ying Liu; Qiang Zhang; Qiang Zhang; Biao Huang; Biao Huang; Xin Li; Tianjiao Liu; Lijuan Xu; Xiaoyan Liao; Jianmei Liao; Wei Cheng; Hui Wang; et al. (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to compare the perioperative outcomes of single-incision laparoscopic surgery (SILS) and dual-port laparoscopic myomectomy in patients with solitary uterine fibroids.MethodsThis retrospective observational study included 162 patients who underwent laparoscopic myomectomy for solitary fibroids from January 2022 to December 2023 at a single tertiary center. Patients were divided into a SILS group (n = 77) and a dual-port group (n = 85). Perioperative outcomes—including operative time, intraoperative blood loss, analgesic use, hospital stay, and cosmetic results—were compared between the groups. Multivariate linear and logistic regression analyses were conducted to identify factors associated with surgical complexity and recovery.ResultsThe dual-port group had significantly lower intraoperative blood loss (41.71 ± 65.37 mL vs. 89.55 ± 93.70 mL, p < 0.001), lower rates of postoperative analgesic use (24.7% vs. 40.3%, p = 0.034), and shorter hospital stays (1.07 ± 0.30 vs. 1.30 ± 0.65 days, p = 0.005) compared to the SILS group. Fibroid size and procedure time were independent predictors of increased bleeding. Posterior wall fibroids were significantly associated with postoperative analgesic use. Delayed discharge was more common in patients with larger fibroids and those requiring postoperative analgesia. Cosmetic outcomes in the dual-port group remained favorable despite the auxiliary incision.ConclusionDual-port laparoscopic myomectomy is a feasible and potentially more effective alternative to single-incision surgery, offering better ergonomic access, improved perioperative outcomes, and excellent cosmetic results. This approach may be especially advantageous when addressing large or posteriorly located fibroids. Individualized surgical planning remains essential to optimize outcomes in minimally invasive myomectomy.